Gerakan Sosial Keagamaan Thariqah ‘Alawiyyin - Ahmad Saepudin (Tsaqofah, 2020)
Religious social movement that the author means a discussion of religious problems does not lie in the controversy found in religious teachings. Nor does it lie in the interpretation of the verses that give guidance on the worship of ubudiyah and syariah muamalah. The emphasis is more on how to influence the process of taking public policy to comply with the sharia. When viewed in terms of the characteristics of social relations, such religious movements can develop social relations that are exclusively closed, in the sense of involving only themselves, or commit monopolistic actions on the various resources they have. But it can also develop social relationships that are inclusive open, in the sense of wanting to engage in movements outside the group, as long as in the spirit of upholding Islamic law. The religious movement through the development of tariqah 'Alawi is now more popular with the movement of the practice of tariqah Al-Haddadiyyah.